Awareness of food safety among street hawkers in Kota Kinabalu Sinsuran night market / Norlaila Sukiran ... [et al.] - Sukiran, Norlaila; Benedict, Stephanie (2011)
The existence of hawker activities in Malaysia can be traced back as early as before independence (Ismail Stapa, 2000). At this time, hawking was not so famous and can only be found in central locations in the city. But day by day, the number of hawkers however increased dramatically after independence. Until today, hawkers are seen as effective and efficient agents in distribution of goods and services especially in food sector. They help to keep the cost of living of the people whether in the rural or urban low by providing food and other consumer items at affordable prices. However buying food at street level involves a lot of risks and this is what the government is concerning right now.